Eliminación de Escherichia Coli resistente a cloro mediante un sistema basado en H2O2 electroquímicamente generado y asistido por UV - Ricaurte Barrero, Laura Paola (Universidad Antonio Nariño, 2023)
In recent years, the inappropriate use of traditional chlorine disinfectant and its derivatives has led to the emergence of resistant bacteria, which represents a major problem for public health globally. Faced with this problem, the evaluation of the effect of a treatment such as the electrochemically generated and UV-assisted H2O2-based system has been carried out, taking advantage of the potential of the hydroxyl radical to inactivate bacteria resistant to chlorine.